Bussiness Development Services (BDS): Menuju Sukses Melalui Laporan Keuangan Dan Perpajakan Untuk Umkm Kota Makassar - Syarifuddin, Safria; Ilham, Ilham; Arifin, Rukminih; Sari, Sri Nirmala; Denka, Veronika Sari (Pakis Journal Institute, 2024)
Business Development Services is a program that allows the General Directorate of Taxation to provide guidance and supervision to MSME taxpayers and their businesses to maximize awareness. Business Development Services is a private institution that operates and is involved in small and medium enterprises (SMEs), as the name implies, the BDS provider institution provides services to improve the business performance and competitiveness of MSMEs. This institution is an institutional instrument aimed at encouraging the advancement of MSMEs, not only in the least developed and developing countries, but olso in the industrialized countries. DGT involves the Pratama Tax Service Office (KPP) in implementing the BDS program directly in the regions. This allows for more personal assistance according to the needs of local MSMEs. With this program, DGT hopes to create a more inclusive tax ecosystem, where MSMEs can develop more optimally while complying with applicable tax obligations. This program is also a form of DGT's commitment to supporting national economic growth through MSME empowerment.